Comparative analysis of mathematics teaching in different studies - Danilenko, Svetlana; Chadyšas, Viktoras; Kasparavičiūtė, Aurelija (Lietuvos matematikos rinkinys, 2016)
The article elaborated the main differences between traditional studies and distance learning. An overview of teaching mathematics of each individual studies in VGTU and comparative analysis are performed.
Keywords: traditional studies; distance learning; teaching mathematics